Hydrochemical study of bottled water in Rwanda and relationship with their origin. Issue 1 (2nd July 2021) - Iyakare, J. D.; Taupin, J-D.; Hitimana, C. N.; Dusabimana, T.; Ghalit, M.; El Ouahabi, M.; Benali, M.; Ngendo, C.; Gharibi, E. K.
Abstract: In Rwanda, commercialized bottled water comes mainly from aquifers located in Rwanda and in neighboring countries. In this study, we compare geochemical parameters of bottled water from the great lakes region and seek to correlate mineralization, hydrochemistry and geological facies of the water reservoir. Based on the results obtained from major ions, trace elements and stable isotopes, 15 bottled waters were analyzed. Bottled waters show low mineralization and various chemical facies, with mainly the dominance of sodium due to the occurrence of alkaline granites in the East Africa region. Bottled water quality was evaluated using various classification systems. All bottled waters show low mineralization attributed to low rock-water interaction with granite, and to unconfined aquifer close to the surface fed by direct infiltration and possibly with high transit fractured circulation. In this region, the very high population density with high agricultural activities lead to strong anthropogenic conditions, but most of the bottled waters do not show any evidence of influence. However, this does not prevent regular control of water quality. Stable water isotopes ( δ 2 H and δ 18 O) highlighted the altitude of aquifers and waters origin of the bottled waters, which is linked to direct rainfall infiltration. HIGHLIGHTS: Adequacy between water quality and its origin. Water bottles are good samples for studying aquifers. Heavy isotope tools to confirm aquifer recharge. Good quality of bottled water in the neighboring countries of the great African lake.